2017
DOI: 10.21273/hortsci12321-17
|View full text |Cite
|
Sign up to set email alerts
|

Growth Is Inversely Correlated with Yield Efficiency across Cultivars in Young Olive (Olea europaea L.) Trees

Abstract: Additional index words. modeling, yield efficiency, partitioning, harvest indexAbstract. The modern olive industry is increasingly interested in olive cultivars that start producing early and remain relatively small, because they are suitable for super highdensity orchards. Some cultivars are better suited to this than others but it is not clear why. Understanding the mechanisms that lead to early production and reduced canopy size is therefore important. The object of this study was to investigate whether dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 31 publications
(44 reference statements)
1
7
0
Order By: Relevance
“…In a previous study (Rosati et al, 2017), we found that tree growth was inversely related to yield efficiency across 12 olive cultivars over a period of several years, thus including adult trees. In that article, causality was not proven, as no defruiting treatments were carried out.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…In a previous study (Rosati et al, 2017), we found that tree growth was inversely related to yield efficiency across 12 olive cultivars over a period of several years, thus including adult trees. In that article, causality was not proven, as no defruiting treatments were carried out.…”
Section: Discussionmentioning
confidence: 74%
“…Given the competition between crop and vegetative growth, we hypothesize that early bearing is implicated in the difference in vigor between such cultivars and more traditional ones that do not fruit until much older. In a previous study (Rosati et al, 2017), we found that tree growth, in terms of both tree diameter and canopy volume increments, was inversely related to tree yield across 12 cultivars in young olive trees. Similarly, Di Vaio et al, (2013) found that across 20 cultivars, the least vigorous tended to have greater early yields.…”
mentioning
confidence: 66%
“…Convincing evidence has been provided that these traits are genetically encoded by the root portion of the grafted plant, playing the rootstock genotype essential roles in shaping variation of these traits in the scion (Warschefsky et al, 2016). In addition, rootstocks can also affect the branching pattern of the scion (Costes et al, 2010) and promote early and more abundant bearing in young olive trees (Rosati et al, 2017(Rosati et al, , 2018. On the one hand, we have verified that all subspecies can be grafted with commercial olive varieties, including cuspidata, which has the maximum genetic distance with europaea ( Supplementary Table S9).…”
Section: Silvolive a Germplasm Collection For The Identification Of mentioning
confidence: 99%
“…Recently, it has been found that deflowering resulted in strong increments in vegetative growth also in young olive trees, and that this eliminated differences in vigor (i.e. vegetative growth) between plants of the cultivar Arbequina (low vigor) and those of the cultivar Frantoio (high vigor), suggesting that cultivar differences in vigor may be explained in terms of different dry matter partitioning towards fruit (Rosati et al, 2017(Rosati et al, , 2018a. This demonstrated that competition for resources plays a major role in determining tree growth in young olive trees, suggesting that tree growth is source limited (Rosati et al, 2018b).…”
Section: Introductionmentioning
confidence: 99%